Narrating Collaborative Music Learning: Teachers’ Lived Experiences in Developing Students’ Musical Abilities - Steffi Eka Permatasari R. A. Ratu; Yosefina Metan; Dersy Rejoice Taneo; Anita Papadja; Ricman Babys (Yayasan Adra Karima Hubbi, 2026)
Background. Music education in junior high schools plays an important role in developing students’ musical skills, creativity, character, and social abilities. However, teaching practices are often dominated by conventional teacher-centered methods, resulting in students’ musical abilities not developing optimally. Therefore, this study aims to examine teachers’ strategies in developing musical abilities through collaborative learning. Purpose. The aim of this study is to determine the strategies used by teachers in developing students’ musical abilities through collaborative learning in classroom practice. Methods. This study employed a qualitative approach using a narrative inquiry design to explore teachers’ experiences in designing and implementing collaborative music instruction at SMP Negeri 4 Taebenu. Data were collected through reflections, classroom observations, and interactions during the research process. Data analysis used narrative thematic analysis based on Braun and Clarke and supported by Clandinin and Connelly’s narrative inquiry framework. Results. Collaborative music learning at SMPN 4 Taebenu is implemented through planning, implementation, and evaluation stages integrated within the Lesson Plan (RPP) adjusted to student characteristics. Strategies are student-centered through group work, inquiry learning, and peer tutoring to increase participation and interaction. Learning activities include rhythmic exercises, music games, and ensemble practice that support experiential learning. Assessment is conducted through observation, interviews, and formative and summative evaluations covering process and outcomes. Challenges include differences in student ability, limited time, and lack of instruments, requiring adaptive strategies and better facilities. Conclusions. Collaborative learning strategies support students’ musical ability development through structured planning and active group participation. Teachers act as facilitators using interactive methods and varied learning media. Existing constraints require institutional support and improved management to strengthen learning effectiveness.